Phantoms - Chappelle, Joe.; Powell, Clifton; Joanna Going; Liev Schreiber; Nicky Katt; Peter O'Toole; Rose Mc Gowan; Ben Affleck (USA Dimension Films, 1998)
In the peaceful town of Snowfield, Colorado something evil has wiped out the community. And now, its up to a group of people to stop it, or at least get out of Snowfield alive.
150 dead and 350 missing in the tiny mountain town of Snowfield, California. And that's only the beginning...
Dean R. Koontz
Languages: Turkish, English Subtitles: Turkish, English
Keywords: Drama; Horror; Thriller